A heteropentanuclear metal string complex [Mo2NiMo2(tpda)4(NCS)2] with two linearly aligned quadruply bonded Mo2 units connected by a Ni ion and a meso configuration of the complex. Issue 83 (3rd October 2016) - Hung, Wei-Chieh; Sigrist, Marc; Hua, Shao-An; Wu, Lai-Chin; Liu, Tsai-Jung; Jin, Bih-Yaw; Lee, Gene-Hsiang; Peng, Shie-Ming
Abstract : This communication describes the meso structure of a heterometallic metal string complex with a high spin Ni(ii ) ion. Abstract : A dimeric molybdenum precursor and nickel ions are used to synthesize a symmetric heteropentanuclear complex, [Mo2 NiMo2 (tpda)4 (NCS)2 ]. This complex possesses unique structural features, as the four ligands are coordinated to the metal framework in a meso configuration. Furthermore, the central Ni 2+ ion is in a high spin state.